2022
DOI: 10.1073/pnas.2118852119
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomics captures dynamic shifts in mycorrhizal coordination in boreal forests

Abstract: Carbon storage and cycling in boreal forests—the largest terrestrial carbon store—is moderated by complex interactions between trees and soil microorganisms. However, existing methods limit our ability to predict how changes in environmental conditions will alter these associations and the essential ecosystem services they provide. To address this, we developed a metatranscriptomic approach to analyze the impact of nutrient enrichment on Norway spruce fine roots and the community structure, function, and tree–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…This can be achieved through expert and accurate annotation of environmental metabarcoding (Anthony et al, 2022), metagenomics (Hagh-Doust et al, 2023, and metatranscriptomic (Auer et al, 2023;Zeng et al, 2023) datasets. The latter approach has been used to examine gene expression in ECM root tips in natural environments, including the effects of anthropogenic N deposition on ECM tree metabolism (Liao et al, 2018;Law et al, 2022;Rivera P erez et al, 2022). Anthony et al (2022) showed that tree growth was linked to the gene copy number of genes involved N uptake and assimilation in associated ECM symbionts.…”
Section: Linking Genes To Ecological Traitsmentioning
confidence: 99%
“…This can be achieved through expert and accurate annotation of environmental metabarcoding (Anthony et al, 2022), metagenomics (Hagh-Doust et al, 2023, and metatranscriptomic (Auer et al, 2023;Zeng et al, 2023) datasets. The latter approach has been used to examine gene expression in ECM root tips in natural environments, including the effects of anthropogenic N deposition on ECM tree metabolism (Liao et al, 2018;Law et al, 2022;Rivera P erez et al, 2022). Anthony et al (2022) showed that tree growth was linked to the gene copy number of genes involved N uptake and assimilation in associated ECM symbionts.…”
Section: Linking Genes To Ecological Traitsmentioning
confidence: 99%
“…Host–microbiome cosequencing: for host-associated microbiomes such as those found in the rhizosphere, human gut, or rumen, sequencing both host and microbial RNA can reveal networks of molecular communication between them (Law et al 2022 ).…”
Section: Approaches For Microbiological Research For the Study Of Mic...mentioning
confidence: 99%
“…We focus on the Map Equation framework and its applications in paleobiology research because it is an increasingly popular alternative to the standard statistical approaches currently used in paleobiology research (Kocsis et al 2021; Rojas et al 2021; Pilotto et al 2022; Viglietti et al 2022). The associated software called Infomap for finding community structure in standard and higher-order networks is also widely used in natural and social sciences (Law et al 2022; Lazaridis et al 2022; Martins et al 2022). The Map Equation framework for higher-order networks combines sedimentological, ecological, morphological, taxonomic, and any other data retrieved from geohistorical records, enabling an integrated investigation of the complex interactions between plate tectonics, global climate change, and evolution of life.…”
Section: Current Challenges and Opportunities For Network-based Paleo...mentioning
confidence: 99%